PEMBUATAN DAN UJI ORGANOLEPTIK SERBUK INSTAN MENTIMUN (Cucumis sativus L.) SEBAGAI ANTIHIPERTENSI DAN PENAMBAHAN JERUK NIPIS SEBAGAI RASA KHAS (Citrus aurantifolia) - Anggraeni, Efi; Djamaluddin, Agus; Ratnasari, Dewi (Journal of Holistic and Health Sciences (Jurnal Ilmu Holistik dan Kesehatan), 2020)
Background. Hypertension or high blood pressure cannot be considered a mild disease. Not only does it reduce the quality of life, but it can be life threatening to sufferers. There are two therapies for hypertension, namely pharmacological and non-pharmacological. Non-pharmacological treatment can be done with traditional medicines in Indonesia that can be used as an alternative treatment for hypertension, namely cucumber and can be combined with lime as a refreshing taste. Then an instant powder preparation from cucumber and lime is made. Purposes. This study aims to determine how to make instant preparations from cucumber and lime as natural anti-hypertension, and to determine the stability and to test the level of preference for the preparations made. Research methods. This study used an action research method in the form of a single treatment arranged in a completely randomized design (CRD). Single treatment was the dose of lime which consisted of 3 levels, namely sample A = addition of 3 ml of lime, sample B = addition of 6 ml of lime, sample C = addition of lime 9 ml. Result. In organoleptic testing all preparations can last for three weeks at room temperature (20?-25?C) then in the hedonic test or preference test sample C the most preferred is 70.8% of the 20 panelists. Conclusion. The addition of lime to each sample affected the taste and the amount of preparation produced differently.